Delovno razmerje za določen čas - Novak, Janez (Podjetje in delo, 2013)
Fixed-term employment is an exception to the rule, i.e. employment contract for an indefinite period of time. Fixed-term employment contract has same legal characteristics as a contract of indefinite duration, with the exception of limited duration. The duration is stipulated by the date or other circumstances (e.g. the execution of works, return of the absent worker etc.). Due to the legal nature and characteristics of a fixed-term employment the legal norms governing such form of employment should be interpreted narrowly and strictly. Also the legal institutes restricting the conclusion offixed-term employment contracts (e.g. objective conditions for such employment form, the prohibition of discrimination and limiting sequential conclusions of multiple fixed-term employment contracts - chaining) should be considered. The article discusses the concept and legal characteristics of a fixed-term employment, the essential characteristics of Employment Relationships Act, case law of the Supreme Court of the Republic of Slovenia and selected judgments of the EU Court.
Keywords: delovna razmerja; delovno pravo; pogodba o zaposlitvi